LANGUAGE STYLE IN MIRACLE FROM HEAVEN MOVIE: A SOCIOLINGUISTIC STUDY - Putri R., Ananda Athira; Halim, Abd; Abdullah, Abdullah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
The researcher analysed the Miracle From Heaven movie. This analysis focused on the use of language style and the factors in the Miracle From Heaven movie. This study aimed to describe the types of language style and describe the factors that influenced the characters in the Miracle From Heaven movie. This study used a descriptive qualitative method and focused on the theory of Martin Joos (1976) and Holmes (2001). Supporting data in this research data was obtained from various references such as journals, books, articles, theses, and online sources. The applied data analysis used interactive model analysis involving data reduction, data display and conclusion (Miles, Hubermen & Saldana, 2014). The results of this study indicated that there are 5 types of language style contained in Miracle From Heaven movie, those were frozen style (1), formal style (9), consultative style (7), casual style (3), and intimate style (20). In addition, this study also showed the factors that influenced the characters’ use is participants, setting, function, and topic.  Keywords— Miracle From Heaven, Language Style